2018
DOI: 10.1051/medsci/20183404014
|View full text |Cite
|
Sign up to set email alerts
|

Établissement du microbiote

Abstract: Some diseases seem to have a developmental origin. Today, the microbiota is recognized as a determinant in health and diseases and one important step is its establishment in the neonate. Some variations in its composition including an imbalance (also called dysbiosis) have been associated to several pathologies. Recent studies suggest a bacterial colonization in the non-pregnant uterus, in the amniotic fluid and in the placenta, which were previously thought sterile. So, during deve-lopmental phases, the fetus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
1
0
2
Order By: Relevance
“…Microorganisms have been found in the majority of placenta, amniotic fluid and umbilical cord, indicating the potential for innate fetal immunity and bacterial tolerance from the newborn [59,93]. Exploration of the endometrial microbiota in infertile women has revealed adverse effects on the functioning of the reproductive system.…”
Section: The Microbiota Of Female and Male Reproductive Systemmentioning
confidence: 99%
“…Microorganisms have been found in the majority of placenta, amniotic fluid and umbilical cord, indicating the potential for innate fetal immunity and bacterial tolerance from the newborn [59,93]. Exploration of the endometrial microbiota in infertile women has revealed adverse effects on the functioning of the reproductive system.…”
Section: The Microbiota Of Female and Male Reproductive Systemmentioning
confidence: 99%
“…Сьогодні цікавими є новітні дослідження щодо ступеня наявності бактерій у плаценті. Існує низка досліджень, які намагались відтворити ці дані [16][17][18][19][20][21][22][23][24][25]. Кілька оглядів підкреслюють, що мікроорганізми у плацентарній тканині не зможуть виживати тривалий час, ураховуючи структуру плаценти та імунобіологічну відповідь господаря [25,26].…”
unclassified
“…В последние годы многочисленные публикации опровергают теорию стерильности внутриутробной среды, так как следы микробов обнаруживаются в плаценте и амниотической жидкости [5,33,34]. Исследование мекония новорожденных показало наличие в нем бактерий, в большей степени энтерококков и стафилококков [33,34]. Возникло множество теорий о передаче материнской микробиоты ребенку еще на стадии беременности, и в первые месяцы после рождения она характеризуется низким разнообразием [5].…”
unclassified